1989
DOI: 10.1007/bf00266668
|View full text |Cite
|
Sign up to set email alerts
|

Genetic improvement of pyrethrum

Abstract: Pyrethrum (Chrysanthemum cinerariefolium), an important paramedicinal plant is a potential source of pyrethrins, which have a long history of safe uses against mosquito larvae - a carrier of malarial parasite. It was introduced in India from Kenya in 1931. Considerable genetic diversity has been generated over the years. Repeated clonal selection could lead to isolation of a number of divergent clones representing selective divergence. Planned hybridization among some of the chosen clones could further enlarge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Breeding programmes have obtained pyrethrum seeds with a germination capacity of 80% (Fulton et al 2001), while wild population seeds have a lower germination capacity. Generally, breeding programs are primarily directed at increasing the concentration of active compounds (Singh and Sharma 1989). So far, experiments have shown that total pyrethrins content of natural Dalmatian pyrethrum are lower than those obtained from commercial selected varieties (Ban et al 2010;Grdiša 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Breeding programmes have obtained pyrethrum seeds with a germination capacity of 80% (Fulton et al 2001), while wild population seeds have a lower germination capacity. Generally, breeding programs are primarily directed at increasing the concentration of active compounds (Singh and Sharma 1989). So far, experiments have shown that total pyrethrins content of natural Dalmatian pyrethrum are lower than those obtained from commercial selected varieties (Ban et al 2010;Grdiša 2013).…”
Section: Resultsmentioning
confidence: 99%
“…For development of a new variety, creation of genetic variability is a pre-requisite. Genetic diversity plays an important role in breeding because hybrids between genetically diverse parents manifest greater heterosis than those between closely related parents [11][12][13][14] . A number of plant breeding methods like cross-breeding, induced mutagenesis and molecular breeding play an important role in the development of new varieties.…”
mentioning
confidence: 99%
“…Creation of genetic variability is pre-requisite for development of new variety. Genetic diversity plays an important role in breeding because hybrids between genetically diverse parents manifest greater heterosis than those between closely related parents [1][2][3][4] . It is important to understand the science behind flower colour inheritance, polyploidy, and potential sterility of one or more parents before hybridization.…”
mentioning
confidence: 99%